2013
DOI: 10.1073/pnas.1303360110
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolidinediones are acute, specific inhibitors of the mitochondrial pyruvate carrier

Abstract: Facilitated pyruvate transport across the mitochondrial inner membrane is a critical step in carbohydrate, amino acid, and lipid metabolism. We report that clinically relevant concentrations of thiazolidinediones (TZDs), a widely used class of insulin sensitizers, acutely and specifically inhibit mitochondrial pyruvate carrier (MPC) activity in a variety of cell types. Respiratory inhibition was overcome with methyl pyruvate, localizing the effect to facilitated pyruvate transport, and knockdown of either para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
270
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 260 publications
(299 citation statements)
references
References 59 publications
17
270
0
Order By: Relevance
“…In this study we showed that MPC can also be inhibited by Zaprinast. Inhibition or knockdown of MPC prevents pyruvate-dependent acetyl-CoA formation and O 2 consumption (5,6,42) and decreases the lactate/pyruvate ratio (43). Our study shows that Zaprinast and UK5099 not only block pyruvate-dependent mitochondrial O 2 consumption and citrate synthesis in brain mitochondria but also cause increases in pyruvate and aspartate and decrease in glutamate in brain mitochondria and the retina.…”
Section: The Effect Of Zaprinast On Glutamate and Aspartate Occurs Inmentioning
confidence: 73%
“…In this study we showed that MPC can also be inhibited by Zaprinast. Inhibition or knockdown of MPC prevents pyruvate-dependent acetyl-CoA formation and O 2 consumption (5,6,42) and decreases the lactate/pyruvate ratio (43). Our study shows that Zaprinast and UK5099 not only block pyruvate-dependent mitochondrial O 2 consumption and citrate synthesis in brain mitochondria but also cause increases in pyruvate and aspartate and decrease in glutamate in brain mitochondria and the retina.…”
Section: The Effect Of Zaprinast On Glutamate and Aspartate Occurs Inmentioning
confidence: 73%
“…1d). We thus tested whether the pyruvate carrier inhibitor (UK5099) 23,24 that perturbs entry of pyruvate into the mitochondria would affect acetate generation. As expected, the 13 C labelled Ac-CoA, Ac-carnitine (reversibly converted from Ac-CoA) and citrate (the first intermediate in the TCA cycle) were decreased by UK5099 treatment ( Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…While their chronic effects are mediated by PPAR-␄ (411), more direct acute effects on mitochondrial bioenergetics have been proposed. Glucose-stimulated respiration of INS-1 832/13 cells and rat islets was inhibited by pioglitazone (278), and specific mechanisms that have been proposed include inhibition of complex I (73,167) and an acute inhibition of the mitochondrial pyruvate transporter (125,342). Each mechanism would have the effect of restricting metabolism and thus indirectly activating AMPK.…”
Section: Amp Kinasementioning
confidence: 99%